Food Safety Alert: Traces of Formalin and Rhodamine B Found in Children's Snacks Near Schools in Lubuklinggau, South Sumatra - Sephia Eka Putri Agustina (Journal of Biotropical Research and Nature Technology, 2025)
Security food is an important global issue, especially in the context of snack child school. The research aims to test the existence of content material addition food, such as formalin and rhodamine B, in snacks school at Public Elementary School 58 Lubuklinggau City. Testing was done using descriptive qualitative with a special test kit to detect formalin and rhodamine B content in various types of snacks. Research results show that all sample snacks from Elementary School 58 Lubuklinggau City negative contain formalin and rhodamine B. This is to signify that snacks sold at SDN 58 Lubuklinggau City are safe for consumption by children, but education for the community still needs to be done to prevent children from snacking carelessly. Education this can give through inspection laboratory tours and activities Communication, Information and Education (KIE) by the POM Center in Lubuklinggau City has contributed positively to increasing awareness among​ the public about choosing safe food​ for children in school.